PRE-HARVEST DESICCATION FOR PRODUCING HIGH QUALITY COWPEA SEEDS - Toledo, Mariana Zampar; Ceccon, Gessí (Chilean Journal of Agricultural & Animal Sciences, 2023)
Pre-harvest desiccation of indeterminate growth habit plants such as cowpea may improve harvest efficiency, uniform maturation and seed quality. This research aimed to determine the effects of pre-harvest desiccation and harvesting time on the yield and quality of cowpea seeds. Two experiments were carried out in Dourados, State of Mato Grosso do Sul, Brazil, in the 2015 and 2017 growing seasons. The experimental design was a split-plot, with main plots arranged as a randomized complete block design, with four replications. Main plots corresponded to the application or no application of paraquat at physiological maturity and subplots to harvesting times: 0, 3, 6. 9, 12 and 15 days after that stage. Moisture content, weight and yield were assessed for each treatment. Physiological quality was evaluated by germination and vigor tests. Means of desiccation conditions were compared by the Tukey test (p?0.05) and harvest times by regression analysis, arranged as a 2x6 factorial. Seed yield and weight were negatively influenced by pre-harvest desiccation with paraquat and delayed harvest. Isolated and interactive responses for desiccation treatments and harvesting time on seed quality varied depending on the growing season. Seed germination and vigor were decreased by late harvest, while desiccation effects varied depending on harvest time.